2019
DOI: 10.1111/epi.16389
|View full text |Cite
|
Sign up to set email alerts
|

Lactate reduces epileptiform activity through HCA1 and GIRK channel activation in rat subicular neurons in an in vitro model

Abstract: Objective: Much evidence suggests that the subiculum plays a significant role in the regulation of epileptic activity. Lactate acts as a neuroprotective agent against many conditions that cause brain damage. During epileptic seizures, lactate formation reaches up to ~6 mmol/L in the brain. We investigated the effect of lactate on subicular pyramidal neurons after induction of epileptiform activity using 4-aminopyridine (4-AP-0Mg 2+ ) in an in vitro epilepsy model in rats. The signaling mechanism associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 53 publications
2
29
1
Order By: Relevance
“…If this is the case, it remains to be demonstrated if lactate exerts dendritic modulation of potassium channels, as a plausible mechanism underlying the EPSP-to-spike coupling. On the other hand, a growing number of works demonstrated that lactate modulates multiple ion channels and modifies the firing discharge and intrinsic excitability [15,17,48,51]. Thus, it is reasonable to assume that lactate may exert specific actions on one synaptic input (RC) and simultaneously exert modulatory actions on the ionic conductances that shape the action potential discharge.…”
Section: Lactate Controls the Output Of Ca3 Pyramidal Cellsmentioning
confidence: 99%
“…If this is the case, it remains to be demonstrated if lactate exerts dendritic modulation of potassium channels, as a plausible mechanism underlying the EPSP-to-spike coupling. On the other hand, a growing number of works demonstrated that lactate modulates multiple ion channels and modifies the firing discharge and intrinsic excitability [15,17,48,51]. Thus, it is reasonable to assume that lactate may exert specific actions on one synaptic input (RC) and simultaneously exert modulatory actions on the ionic conductances that shape the action potential discharge.…”
Section: Lactate Controls the Output Of Ca3 Pyramidal Cellsmentioning
confidence: 99%
“…Due to the Warburg effect, a process unique to cancer cells, LA can be produced and accumulate extensively in tumors [1]. It is currently thought that in addition to simply supplying energy, excessive LA performs other physiological functions, such as regulating immunity, metabolism and angiogenesis [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Exogenous lactate may also act as an inhibitor in hippocampal neurons. According to a recent research, exogenous lactate induced outward currents mediated by G protein-gated inwardly rectifying potassium(GIRK) through activating GPR81, resulting in hyperpolarization and epileptiform firing decreasing in the subicular neurons of hippocampal slices ( Figure 2C) (84). Furthermore, lactate could regulate some ion channels by decreasing pH.…”
Section: Lactatementioning
confidence: 90%
“…(B) Lactate over physiological levels acted as an inhibitor for cortical neurons a GPR81-mediated pathway(81)(82)(83). (C) Exogenous lactate (over physiological levels) induced an outward current mediated by G protein-gated inwardly rectifying potassium (GIRK) through activating GPR81, resulting in hyperpolarization and epileptiform firing decrease in the subicular neurons(84). (D) Lactate could regulate acid-sensing ion channel−1a (ASIC1a) by decreasing pH to Stimulate inhibitory neuronal excitation(85).…”
mentioning
confidence: 99%